Stiffness and buckling analysis of variable stiffness laminates including the effect of automated fibre placement defects. (15th October 2019) - Mishra, Vibhas; Peeters, Daniël M.J.; Abdalla, Mostafa M.
Abstract: Composite materials are finding increasing application, for example in commercial aircraft. Traditionally fiber angles are constant in a single layer. Currently, so called variable stiffness panels with steered fibres, where the angle is changing within a layer are investigated. These panels are usually manufactured using automated fibre placement machines. Since the fibre angle is changing, and the tow paths are shifted as a whole in a single direction, gaps and/or overlaps between consecutive tows are created. This paper explores the effect of these gaps on the stiffness and buckling load of variable stiffness panels. A methodology is presented using homogenization to account for the gaps in a computational efficient way. The result shows that the stiffness results are on conservative side and are within 5% accuracy. However, the buckling results are on the unconservative side. The computational cost of the pre-processing of the proposed method is 45 times lower than the cost of the defect-ply method presented in the literature.